Experience the Truth According to Heart: An Analysis of Kien Minagawa’s Reflection Sixth in the Abstract of Inquiry and Study - Heng, Shen (Sinología hispánica. China Studies Review, 2018)
Kien Minagawa is a Sinologist in Japanese Tokchon middle age. Abstract of Inquiry and Study is the learning principal of Kien Minagawa, which containing Six Clauses and Thirty Subclauses. Reflection is the last step of Six Clauses, and it is not only the end and summary of the article, but also the beginning of learning. Reflection contains three stages: observing, thinking and practise, which depend on each other. The three stages of Reflection are the study of the subtle relationship between knowledge and practice, and also the learning for oneself.